PROBABILISTIC NUMERICAL CHARACTERISTICS OF OVERHEAD CRANES LOADS ON INDUSTRIAL BUILDINGS FRAMEWORKS - Pichugin S.F., S. F.; Patenko, Yu. E.; Maslova, S. A. (Academic journal Industrial Machine Building Civil Engineering, 2018)
The article is dedicated to the development of analytical model of loads four-wheels travelling cranes loads. The design values of mathematical expectation, variance and standard for vertical and horizontal component of crane load were received. Numerical example has shown that the values of analytical numerical characteristics are very close to the experimental values of loads, and can be applied in the reliability estimation. Analytical numerical characteristics are used in the of steel framework one-storey industrial building columns calculation reliability. The time factor and the stochastic nature of the loads and the strength of steel were considered. The effect of different parameters (cranes capacity and the mode of travelling cranes, columns step, type of connection the column and girder, the type of roofing and the values of wind and snow loads) on the reliability of steel frameworks was considered.